Carbonic anhydrase polymorphism in West African Dwarf goat populations of western Nigeria (2022)
Carbonic anhydrase polymorphism in West African Dwarf (WAD) goat populations, from Oyo and Ogun States was investigated using the cellulose acetate electrophoresis system. Blood samples of 5 mL were collected from 60 WAD goats (30 from Ibadan (Oyo State) and 30 from Ijebu-Ode (Ogun State), via the jugular veins and placed into heparinised bottles. The results of the electrophoresis analyses were subjected to statistical analysis using Tools For Population Genetic Analysis (TFPGA) software. The results revealed that two alleles, CAF and CAS govern the three genotypes (CAFF, CAFS and CASS) with CASS being prevalent. Allele frequencies ranged from 0.24 for CAF in Ijebu-Ode to 0.76 in CAS also from Ijebu-Ode while the genotype frequencies ranged from 0.09 in CAFF from Ijebu-Ode to 0.61 in CASS also from the Ijebu-Ode population. Deviation from the Hardy-Weinberg equilibrium was significant (P ≤ 0.05) in the population from Ibadan. Average gene diversity was 0.43, while the expected heterozygosity HE(0.47) was higher than the observed heterozygosity HO(0.25).Wright analysis showed that the populations sampled were from inbred populations with a positive FIT and FIS value (0.47, and 0.06 respectively) implying deficiency in heterozygote and the FST value of 0.45 indicating greater genetic differentiations among the populations giving opportunity for improvement.